Salicylic acid and reactive oxygen species interplay in the transcriptional control of defense genes expression - Herrera-Vásquez, Ariel; Salinas, Paula; Holuigue, Loreto (Frontiers in Plant Science, 2015)
It is well established that salicylic acid (SA) plays a critical role in the transcriptional reprograming that occurs during the plant defense response against biotic and abiotic stress. In the course of the defense response, the transcription of different sets of defense genes is controlled in a spatio-temporal manner via SA-mediated mechanisms. Interestingly, different lines of evidence indicate that SA interplays with reactive oxygen species (ROS) and glutathione (GSH) in stressed plants. In this review we focus on the evidence that links SA, ROS and GSH signals to the transcriptional control of defense genes. We discuss how redox modifications of regulators and co-regulators involved in SA-mediated transcriptional responses control the temporal patterns of gene expression in response to stress. Finally, we examine how these redox sensors are coordinated with the dynamics of cellular redox changes occurring in the defense response to biotic and abiotic stress.